Surgical techniques for the management of male infertility - Lopushnyan, Natalya A (Nature Publishing Group, 2012)
Evaluation and surgical treatment of male infertility has evolved and expanded, now leading to more precise diagnoses and tailored treatments with diminished morbidity and greater success. Surgeries for male infertility are divided into four major categories: (i) diagnostic surgery; (ii) surgery to improve sperm production; (iii) surgery to improve sperm delivery; and (iv) surgery to retrieve sperm for use with in vitro fertilization and intracytoplasmic sperm injection (IVF–ICSI). While today we are more successful than ever in treating male infertility, pregnancy is still not always achieved likely due to factors that remain poorly understood. Clinicians treating infertility should advocate for couple-based therapy, and require that both partners have a thorough evaluation and an informed discussion before undergoing specific surgical therapies.